2022
DOI: 10.1021/acs.jpcc.1c08743
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Mg–Sc–H Phase Diagram and Its Superconductivity from First-Principles Calculations

Abstract: In this work, a global search for crystal structures of ternary Mg–Sc–H hydrides (Mg x Sc y H z ) under high pressure (100 ≤ P ≤ 200 GPa) was performed using the evolutionary algorithm and first-principles calculations. On their basis, we computed the thermodynamic convex hull and pressure-dependent phase diagram of Mg x Sc y H z for a wide range of compositions (x + y = 2, 3, 4 and z = 2–12, 14, 16, 18). Our crystal structure search and convex hull analysis revealed no thermodynamically stable compounds in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 65 publications
1
13
0
Order By: Relevance
“…32 Also, very recently, Mg-substituted systems have led to predictions of ternary Mg-Sc-H phase. 30 These findings apparently indicate the crystal structure of MgScH 6 shows superconductivity with T c of 41 K at a pressure of 100 GPa. Apart from superconductivity in Hrich materials, carbonaceous sulfur hydride (C-S-H) emerges as a promising candidate in the high-pressure society as it is demonstrated in the experiment to be superconducting at a T c approaching room temperature.…”
mentioning
confidence: 82%
See 2 more Smart Citations
“…32 Also, very recently, Mg-substituted systems have led to predictions of ternary Mg-Sc-H phase. 30 These findings apparently indicate the crystal structure of MgScH 6 shows superconductivity with T c of 41 K at a pressure of 100 GPa. Apart from superconductivity in Hrich materials, carbonaceous sulfur hydride (C-S-H) emerges as a promising candidate in the high-pressure society as it is demonstrated in the experiment to be superconducting at a T c approaching room temperature.…”
mentioning
confidence: 82%
“…It is, moreover, worth noting that magnesium has the potential to form an H‐rich phase, that is, the sodalite‐like MgH 6 is stable above 263 GPa 32 . Also, very recently, Mg‐substituted systems have led to predictions of ternary Mg‐Sc‐H phase 30 . These findings apparently indicate the crystal structure of MgScH 6 shows superconductivity with T c of 41 K at a pressure of 100 GPa.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…But then multi-component hydrides contain more combinations of elements, they are more promising in the search for high(room)-temperature superconductivity. [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59] For example, magnesium hydride can dissociate the H 2 molecule into atomic H by lithium doping, thus increasing its electron concentration at the Fermi level (E F ), enabling it to reach a T c value of 473 K at 250 GPa. [47] Furthermore, recent research has revealed that a small amount of carbon doping in H 3 S can result in room superconductivity (T c = 287.7 ± 1.2 K at 267 ± 10 GPa).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the superconductivity of ternary clathrate hydride has also attracted a lot of attention, and most of them cover the hydrides of alkaline-earth metals and rare-earth metals. [9,[31][32][33][34][35][36][37][38][39][40][41] Although the theoretically predicted T c of Li 2 MgH 16 composed of alkali and alkaline-earth metals at 250 GPa is 473 K, its enthalpy of formation lies above the convex hull [8,42] and its synthesis in experiment is still a great challenge. It is noteworthy to mention that partial replacement of La atoms by magnetic Nd atoms results in significant suppression of superconductivity in LaH 10 .…”
Section: Introductionmentioning
confidence: 99%